Dimethylformamide-stabilised palladium nanoclusters catalysed coupling reactions of aryl halides with hydrosilanes/disilanes. Issue 30 (3rd June 2019) - Nagata, Tatsuki; Inoue, Takeru; Lin, Xianjin; Ishimoto, Shinya; Nakamichi, Seiya; Oka, Hideo; Kondo, Ryota; Suzuki, Takeyuki; Obora, Yasushi
Abstract : A highly efficient and reusable Pd NCs catalyst system for silylation of aryl halides was developed. Abstract : N, N -Dimethylformamide-stabilised Pd nanocluster (NC) catalysed cross-coupling reactions of hydrosilane/disilane have been investigated. In this reaction, the coupling reaction proceeds without ligands with low catalyst loading. N, N- Dimethylacetamide is a crucial solvent in these reactions. The solvent effect was considered by various techniques, such as transmission electron microscopy, X-ray photoelectron spectroscopy, and thermogravimetric analysis. The Pd NCs can be recycled five times under both hydrosilane and disilane reaction conditions.